2019
DOI: 10.1177/0284185119847675
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and imaging assessment and treatment of hallux valgus

Abstract: Hallux valgus is a common condition estimated to affect as many as 23% of adults. The condition is associated with a variety of debilitating symptoms leading to significant morbidity and quality of life issues. Proper evaluation of this deformity and the timely management of its symptoms can improve hallux valgus-related symptomatology and quality of life. The most commonly used and readily reproduced measurements for assessing hallux valgus are the inter-metatarsal angle and the hallux valgus angle. These ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 49 publications
0
13
0
1
Order By: Relevance
“…HVA, IMA, metatarsophalangeal osteoarthritis, metatarsal rotation, and lateral round sign of first metatarsal present are among these evaluations. Besides radiographic measurements, clinical evaluation methods such as quality of life can guide the definition and optimal treatment of HV deformity [23].…”
Section: Discussionmentioning
confidence: 99%
“…HVA, IMA, metatarsophalangeal osteoarthritis, metatarsal rotation, and lateral round sign of first metatarsal present are among these evaluations. Besides radiographic measurements, clinical evaluation methods such as quality of life can guide the definition and optimal treatment of HV deformity [23].…”
Section: Discussionmentioning
confidence: 99%
“…The research enriched our understanding of the morphology and pathology of HV, defined a safe range of hallux operations, and improved the understanding of HV for young clinical orthopaedic surgeons. Hallux valgus is not only a deformity with medial deviation of the first metatarsal and lateral deviation of the sesamoids but also widely considered a triplanar deformity, with involvement of the transverse, sagittal, and frontal planes 6,12 . The literature describes many treatment strategies for HV with the same degree of severity.…”
Section: Discussionmentioning
confidence: 99%
“…Hallux valgus is not only a deformity with medial deviation of the first metatarsal and lateral deviation of the sesamoids but also widely considered a triplanar deformity, with involvement of the transverse, sagittal, and frontal planes 6, 12 . The literature describes many treatment strategies for HV with the same degree of severity.…”
Section: Discussionmentioning
confidence: 99%
“…The original balance of the muscle strength of the metatarsal bone promotes the metatarsal rotation during the relative displacement of the sesamoid bone. The sesamoids on the head of the rst metatarsal are in dynamic balance because of pulling by two group muscles [31] . So in theory, either sesamoid dislocation could lead to hallux valgus [32][33] .In this study, it was found that the normal position of sesamoid bone (FSP) intersected with the lateral cortex of the rst metatarsal bone accounted for (52.3 ± 3.2) % of the total area of sesamoid bones.…”
Section: Correlation Between Tibial Sesamoid Bone and Hallux Valgusmentioning
confidence: 99%